Republic of Madagascar : Technical Assistance Report-Government Finance Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance paper on the Republic of Madagascar explains the need for the Malagasy authorities to adopt the Government Finance Statistics Manual (GFSM) 2014 concepts, definitions, and methodology as part of the macroeconomic statistics improvement Project. The report recommends that it is important to improve macroeconomic analysis and monitoring of the overall impact of government finances on the country's economy, something that other public finance 'figures' of a budgetary and accounting nature are not intended to do. The report shows that steady progress continues with the preparation of a bridge table between the chart of accounts and the GFSM 2014 classifications. Notable improvements have been made in the presentation of Other Net Treasury Operations, the detailed components of which were identified and can now be presented on a gross basis. Based on the progress made, the prospect of compiling consolidated GFS covering all subsectors of the Malagasy general government in a not-too-distant future is encouraging.